KOMPOSISI KIMIA SUBSTRAT ASOSIASI Sonneratia alba - Avicennia marina DI MUARA SUNGAI LEKOK KABUPATEN PASURUAN - Hani Sudarmanto; Mas Loegito; Trisnadi Widyoleksono C.P.; Handoko Darmokoesoemo; Sediono (The East Java Biological Society, 1997)
The mangrove forest occurred in the north coast of Pasuruan Regency have not been reported about the vegetational and substrate compositions. The research's purpose were to analysis the vegetational composition and the chemical properties of the substrate. The result showed that this mangrove forest were dominated by association of Sonneratia alba - Avicennia marina. The result showed that soils had the natural reaction (pH 7.01-7.65), low in organic matter (2.18-4.27%) and total nitrogen (0.48-0.51%), but high in total phosphorus (15.19-29.22 ppm) and in exchangeable cation (Ca2+: 389.855-504.065 mg/100 gr, Mg2+: 409.522-441.400 mg/100 gr, K+: 228.900-390-435 mg/100 gr).